THE EFFECTS OF SYNCHRONIZATION OF CARBOHYDRATE AND PROTEIN SUPPLY IN SUGARCANE BAGASSE BASED RATION ON BODY COMPOSITION OF SHEEP - Wati, N. E.; Nuswantara, L. K.; Wahyono, F.; Pangestu, E.; Achmadi, J. (Diponegoro University, 2015)
The objective of this research was to study the effects of synchronization of carbohydrate and protein supply in sugarcane bagasse based ration on the body composition of sheep. The studywasconsistedoftwo steps of experiment. The first step of experiment used two rumen cannulated adult rams to create formulation of three diets with different synchronization index, namely 0.37; 0.50 and 0.63 respectively. The experimental diets were designed to be iso-energy, iso-nitrogenous and iso-neutral detergent fibre (iso-NDF). The second step of experiment was to determine the body composition of sheep fed the experimental diets, which were created in the first experiment. The body composition of fifteen rams were determined on week 0; 4; and 8 of experimental period, these were accomplished using the technique of urea dilution. The alteration of synchronization index did not affect on feed intake, ratio of ruminal acetate to propionate and serum glucose concentration, but dry matter (DM) digestibility was affected (P<0.05) by the treatment of synchronization index in the diet. The alteration of synchronization index in the diet did not affect on the percentage of body protein, fat and water significantly, though body weight of sheep gained slightly during the experimental period.